`Kandungan Protein dan Abu Tanaman Alfalfa( Medicago sativa L) setelah Pemupukan Biorisa - Parman, Sarjana - (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2007)
The reasearch is about protein and ash content in Alfalfa ( M.sativa L ) after fertilization bioriza-02. Thisresearch is in polibag plastic in 15 March-15 August 2006, using to research design RAL ( Randomized CompleteDesign ), Treatmen is give fertilization biorisa–02 , one treatment is Po ( without biorisa ) P1 ( Biorisa-02 0,5 caps/plant ), P2 (1 caps/plant); P3;(11/2 caps/plant) and P4 (2 caps / plant) every treatment repeated five times . Proteinconternt and ash analysed follow of makro-Kjeldahl which modification (AOC, 1970 in Sudarmaji, 1984). The resultof research indicated that increase of dose of fertilization biorisa-02 will boost up rate of protein of crop alfalfa,though fertilization of dose Po (without biorisa–02 caps/plant) 18,472 mg/100 of gram differ is not real by control18.264; so also fertilization 1 caps/plant ( 20,786 ) differing is not real with fertilization have dose (20,82) but differreality with gift fertilize to have dose 2 mg/plant (21,828)